Tristin Dorsey: capstone - Dorsey, Tristin, artist (Colorado State University. Libraries, 2025)
The artist's statement: I am not interested in the fixed singularity of any work. I morph and change my paintings throughout the process of creation as well as in the installation of the work itself. Because my work consists of a multitude of fragments, I install the paintings in different compositions, eliciting a malleability and responsiveness that is not typical of stretched canvas, collaged, or otherwise traditional paintings; Whether they are installed as a formal composition on the wall, rolled up and displayed (concealing the painted surface), or layered on the ground. The paint itself is stuck but given mobility, it changes, reacts, no longer a fixed image-serving material. This body of work begins with large dropcloth canvases, which I tear into panels or fragments. These canvas fragments are worked, peeled apart, worked and layered again, eventually forming a collection. Each time I exhume a panel from the stack, it becomes both a brand new object and one that bears its own past. The canvas fragments hold onto the paint from the painting before and the painting after; left behind are echoes of these interactions. Aesthetically resulting in an archeology-like reframing of historical abstract lineages. The visual database of abstraction as material becomes an object dug up and reprocessed, like a corpse or a long forgotten tool. The outcome is a deeply layered and thick amalgamation of paint as material, not as image; An examination of the objecthood, ontology, and materiality of paint. I am exploring the history of abstraction, its context today as an institutionally upheld but often gatekept art form, and furthering it along through experimental methods and archeological practices. I am working to explore the energy that a painting holds as an object, its contextual weight, and its connotation as a medium rather than for imagery purposes. The work is an archive of continuous labor and practice.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting